2020
DOI: 10.1002/smi.3016
|View full text |Cite
|
Sign up to set email alerts
|

Stress and sleep in college students prior to and during the COVID‐19 pandemic

Abstract: Within the short timeframe of the COVID‐19 pandemic, there has been increasing interest in its potential impact on psychological stress and sleep. Using standardized self‐report measures, we examined differences in stress and sleep by comparing responses from three independent samples of undergraduates in the United States. Samples were obtained prior to COVID‐19 (Spring 2019) and at two periods during the pandemic (Spring 2020 and Summer 2020) which corresponded to an increasing impact of COVID‐19 at the loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
118
8
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(145 citation statements)
references
References 53 publications
(74 reference statements)
10
118
8
9
Order By: Relevance
“…Interestingly, pandemic-related stress was not significantly associated with sleep quality, and current research examining this relationship, particularly in US adult civilians, remains unclear (Benham, 2020;Kim-Godwin et al, 2021;Tsang et al, 2021;Ulrich et al, 2021). Our results instead suggest that resilience and coping during the coronavirus pandemic may influence sleep quality more than pandemic-related stress, which presents interesting applied implications.…”
Section: Discussioncontrasting
confidence: 54%
“…Interestingly, pandemic-related stress was not significantly associated with sleep quality, and current research examining this relationship, particularly in US adult civilians, remains unclear (Benham, 2020;Kim-Godwin et al, 2021;Tsang et al, 2021;Ulrich et al, 2021). Our results instead suggest that resilience and coping during the coronavirus pandemic may influence sleep quality more than pandemic-related stress, which presents interesting applied implications.…”
Section: Discussioncontrasting
confidence: 54%
“…For example, some studies indicated that female college students tend to use heroin more rapidly, thus becoming addicted to it in a shorter period compared to male students (19). In addition, previous studies indicated that college students were at high risk for poor sleep quality during the COVID-19 so that frequently taking medicine such as sleep pills and antalgic is a common phenomenon among these students (20)(21)(22). Previous studies also identified both female and male substance abusers that are usually diagnosed with emotional disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Also, there is evidence of greater sleep latency and poorer sleep efficiency during the pandemic. 13,17 Especially, undergraduate medical students have poor sleep quality, internet addiction, and depression. [18][19][20] Sufficient studies have not been done in Nepal regarding the sleep quality of medical students during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%